Promising Cytotoxicity and Anticancer Activity of Capsicum Annuum - Ali Al-Samydai; Hanan Azzam; Farah Al-Mamoori; Deniz M. Al-Tawalbe; Bashaer Abu-Irmaileh; Talal Aburjai; Yasser Khalil Bustanji (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: Cancer is the second leading cause of death globally. Most of the anticancer drugs showed poorselectivity. Medicinal plants have proven, historically, their value as a source of molecules with therapeuticpotential. Aim and objective: This study aims to optimize the method of extraction, identification, qualitativeand quantitative analysis of Capsaicin (CAP) from Jordanian Capsicum annuum (C. annuum), and toinvestigate the anticancer activity of the crude extract.Methods: The plants extract from C. annuum wasobtained by Soxhlet extraction, HPLC were used for qualitative and quantitative analysis, and Cytotoxicpotentials was investigated by Cell viability (MTT).Results: Our results showed that Hexan solventrepresented a convenient yield of extraction and the highest percentage of CAP yield with better purity ofextract in comparison with other solvents, Jordan Valley ‘’Al-Ghor’’ showed the highest percentage of CAPyield in extract. Additionally, C. annuum crude extract showed dose depended cytotoxicity activity againsta cancer cell. Conclusion, we have optimized the isolated, qualitative and quantitative analysis of CAP fromthe fruits of C. annuum growing in Jordan in fast and reproducible method.